The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1756-185x.14382
|View full text |Cite
|
Sign up to set email alerts
|

Is collagen supplementation friend or foe in rheumatoid arthritis and osteoarthritis? A comprehensive systematic review

Abstract: Rheumatoid arthritis (RA) and osteoarthritis (OA) both are chronic diseases affecting joints. Immune response against collagen in both diseases may have a role in the initiation and progression of the disease. There is a hypothesis that suppression of immune response vs collagen could be a therapeutic approach in RA and OA. Exposure of gut immune system to collagen is a way to suppress immune response against collagen in the joints. So, the current systematic review is aimed to evaluate the effects of collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This modulation of the natural immune reaction is an important support for the anti-inflammatory activity and provides an environment conducive to cartilage repair. Moreover, it could be involved in the occurrence of adverse effects, which was elevated in human studies [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…This modulation of the natural immune reaction is an important support for the anti-inflammatory activity and provides an environment conducive to cartilage repair. Moreover, it could be involved in the occurrence of adverse effects, which was elevated in human studies [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treated group showed a reduction in IL-8, IL-6, and IL-10 levels. Despite the possible beneficial effects of collagen supplementation, studies have also shown adverse effects of collagen supplementation in patients with RA or OA, as well as a low efficiency of collagen treatment compared to routine treatments [56].…”
Section: Osteoarthritis Bone Regeneration and Osteoporosismentioning
confidence: 99%
“…However, the level of evidence is low, and heterogeneity is evident [87]. There was insufficient evidence to support collagen supplementation in RA [88].…”
Section: Nutritional Therapymentioning
confidence: 99%